2021
DOI: 10.3390/pharmaceutics13050616
|View full text |Cite
|
Sign up to set email alerts
|

Stereolithography Apparatus Evolution: Enhancing Throughput and Efficiency of Pharmaceutical Formulation Development

Abstract: Pharmaceutical applications of 3D printing technologies are growing rapidly. Among these, vat photopolymerisation (VP) techniques, including Stereolithography (SLA) hold much promise for their potential to deliver personalised medicines on-demand. SLA 3D printing offers advantageous features for pharmaceutical production, such as operating at room temperature and offering an unrivaled printing resolution. However, since conventional SLA apparatus are designed to operate with large volumes of a single photopoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It was found that SLA reduced thermal drug degradation compared to FDM [ 61 ]. However, the main reason holding back the application of SLA in pharmaceuticals is the limited number of photocrosslinkable polymers that are safe for pharmaceutical use [ 62 ]. There could be potential hazards from the use of resins such as carcinogenicity, which need to be identified in the future.…”
Section: 3d-printing Techniquesmentioning
confidence: 99%
“…It was found that SLA reduced thermal drug degradation compared to FDM [ 61 ]. However, the main reason holding back the application of SLA in pharmaceuticals is the limited number of photocrosslinkable polymers that are safe for pharmaceutical use [ 62 ]. There could be potential hazards from the use of resins such as carcinogenicity, which need to be identified in the future.…”
Section: 3d-printing Techniquesmentioning
confidence: 99%
“…The material used in the Stereolithography apparatus (SLA) is photosensitive thermoset polymers [21], the first developed 3D printing technology that uses photopolymerization for 3D printing and cures the resin by absorbing photopolymerization triggered by light [22]. The principle of the architecture is to reuse the resin cured layer by layer, printing the desired product layer by layer.…”
Section: Figure 3 Advantages and Disadvantages Of Slsmentioning
confidence: 99%
“…This technique requires a large amount of energy from the laser used and is affected by the corresponding power of the light source, the scanning speed, the exposed material, and the polymer and photoinitiation dose [30,36,55]. Presently, the most commonly used photoinitiator is diphenyl (2,4,6-trimethyl-benzoyl) phosphine oxide (TPO) [56]. Unlike FDM technology, SLA technology can be used to print at room temperature and is suitable for printing formulations with heat-sensitive drugs (which can reduce drug degradation) [6,56].…”
Section: Stereo Lithography Appearance (Sla)mentioning
confidence: 99%
“…Presently, the most commonly used photoinitiator is diphenyl (2,4,6-trimethyl-benzoyl) phosphine oxide (TPO) [56]. Unlike FDM technology, SLA technology can be used to print at room temperature and is suitable for printing formulations with heat-sensitive drugs (which can reduce drug degradation) [6,56]. For example, one group of researchers dissolved a drug in different mixtures of polyethylene glycol diacrylate (PEGDA) and polyethylene glycol (PEG), which were then cured in the presence of a laser beam to prepare a drug delivery device (with a nasal shape) with higher resolution and higher drug loading (1.9% w/w) and no drug degradation compared to a device prepared via FDM [57].…”
Section: Stereo Lithography Appearance (Sla)mentioning
confidence: 99%